2016
DOI: 10.13168/agg.2016.0010
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of time_changeable seasonal components in the GPS height time series: A case study for Central Europe

Abstract: Nowadays, beyond the dispute we should take into account the time-varying parameters of seasonals in the GPS-derived position time series. Either real geophysical effects or systemspecified artefacts can introduce non-sinusoidal changes. For this study, we used 18 daily position time series from Central European stations provided by the Jet Propulsion Laboratory (JPL) processed in the GIPSY-OASIS software in a Precise Point Positioning (PPP) mode. We tested two different approaches to subtract the seasonal sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In this section we only discuss the amplitudes and phases of annual and semi-annual tropical and draconitic periods, as these contribute the most to GPS data. As was shown by Gruszczynska et al (2016), the tropical annual signal (365.25 days) may obvious power-law behaviour close to flicker noise between low frequencies up to approximately 100 cpy. Moving towards the end of the spectrum, the PSD becomes flat, revealing a pure white noise in the highest frequencies.…”
Section: Seasonal Signalsmentioning
confidence: 54%
“…In this section we only discuss the amplitudes and phases of annual and semi-annual tropical and draconitic periods, as these contribute the most to GPS data. As was shown by Gruszczynska et al (2016), the tropical annual signal (365.25 days) may obvious power-law behaviour close to flicker noise between low frequencies up to approximately 100 cpy. Moving towards the end of the spectrum, the PSD becomes flat, revealing a pure white noise in the highest frequencies.…”
Section: Seasonal Signalsmentioning
confidence: 54%
“…These residuals were then subjected to CME estimates. In this research, we intentionally focused on annual period, as the percentage of total variance of time series explained by modes of annual signal is much higher than the variance explained by any other pair of modes (Gruszczynska et al 2016).…”
Section: Common Seasonal Signals Estimated From Environmental Loadingsmentioning
confidence: 99%
“…Few methods such as Singular Spectrum Analysis (SSA), Wavelet Decomposition (WD) and Kalman Filter (KF) have been already used to retrieve stationdependent time-varying curves from the GPS position time series (Chen et al 2013;Gruszczynska et al 2016;Didova et al 2016;Klos et al 2018a). However, neither of them is able to separate real and spurious effects from the GPS data.…”
Section: Introductionmentioning
confidence: 99%
“…Klos et al (2018c) demonstrated that the seasonal signals in loading models do not remain constant over time. This means that the seasonal changes in the GPS position time series may be also time-variable (Freymueller 2009;Chen et al 2013;Bogusz et al 2015a;Gruszczynska et al 2016). Therefore, amplitudes given as constants over time, typically derived with the weighted least-squares method, do not provide the most accurate description of them.…”
Section: Introductionmentioning
confidence: 99%
“…They noted that the effect of the remaining peaks was insignificant to the noise analysis. Xu and Yeu (2015) and Gruszczynska et al (2016) proposed using the singular spectrum analysis (SSA) approach to model the time-varying curves. Chen et al (2013) compared the estimates obtained with the SSA and Kalman filter (KF) techniques, and emphasized that the SSA is much faster than the KF and features a lower computational cost.…”
Section: Introductionmentioning
confidence: 99%